Meta-analyses of Culex blood-meals indicates strong regional effect on feeding patterns. - Jet S Griep; Eve Grant; Jack Pilgrim; Olena Riabinina; Matthew Baylis; Maya Wardeh; Marcus S C Blagrove (PLoS Neglected Tropical Diseases)
Understanding host utilization by mosquito vectors is essential to assess the risk of vector-borne diseases. Many studies have investigated the feeding patterns of Culex mosquitoes by molecular analysis of blood-meals from field collected mosquitoes. However, these individual small-scale studies only provide a limited understanding of the complex host-vector interactions when considered in isolation. Here, we analyze the Culex blood-feeding data from 109 publications over the last 15 years to provide a global insight into the feeding patterns of Culex mosquitoes, with particular reference to vectors of currently emerging Culex-borne viruses such as West Nile and Usutu. Data on 29990 blood-meals from 70 different Culex species were extracted from published literature. The percentage of blood-meals on amphibian, avian, human, non-human mammalian, and reptilian hosts was determined for each Culex species. Our analysis showed that feeding patterns were not significantly explained by mosquito species-level phylogeny, indicating that external factors play an important role in determining mosquito feeding patterns. For Cx. quinquefasciatus, 'Cx. pipiens pooled', and Cx. tritaeniorhynchus, feeding patterns were compared across the world's seven biogeographical realms. Culex tritaeniorhynchus, 'Cx. pipiens pooled' and Cx. quinquefasciatus all had significantly varied feeding patterns between realms. These results demonstrate that feeding patterns of Culex mosquitoes vary between species but can also vary between geographically distinct populations of the same species, indicating that regional or population-level adaptations are major drivers of host utilization. Ultimately, these findings support the surveillance of vector-borne diseases by specifying which host groups are most likely to be at risk.